39.3k views
20 votes
2. given 2x2 system
X + y - Z=3
2y + 2z = 6
-2y - Z = -2

1 Answer

12 votes

Answer:

Explanation:

X + y - Z=3 ------------------(I)

2y + 2z = 6 ------------------(II)

-2y - Z = -2 ------------------(III)

Multiply equation (III) by 2 and add equation (II) & (III)

(II) 2y + 2z = 6

(III)*2 -4y - 2z = -4 {Now add and z will be eliminated}

-2y = 2

y = 2/-2

y = -1

Plugin y =-1 in equation (II)

2*(-1) + 2z = 6

-2 + 2z = 6

2z = 6 + 2

2z = 8

z = 8/2

z = 4

Plugin y = -1 & z = 4 in equation(I)

x - 1 - 4 = 3

x - 5 = 3

x = 3 + 5

x = 8

User Paul Stengel
by
5.1k points